Trial by Fire - Jance, Judith A. (New York : Pocket Star Books, 2011)
Taking a media relations position with the Yavapai County Police Department, former television journalist Ali Reynolds investigates a subdivision fire and the identity of an injured amnesiac woman, a case that unleashes a remorseless killer.
Keywords: Reynolds, Ali (Fictitious character) -- Fiction; Arizona -- Fiction; Detective and mystery fiction